Pengelolaan Iklim Sekolah dalam Menunjang Kinerja Guru (Studi Kasus SMA Tamansiswa Pematangsiantar) - Sofian Sofian (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
This study aims to determine the physical management, social environment and the role of the principal in managing the school climate to support teacher performance at SMA Tamansiswa. A conducive climate marked by the creation of a physical school environment including an environment inside and outside the classroom as a place to carry out learning activities at school has been managed effectively, providing comfort, fun, joy, and health for teachers at work so that the teaching and learning process can take place. well. The social environment that has been built in the school is to develop good attitudes and behavior. The teachers show a sympathetic attitude and behavior, provide support and motivation to students, and set a good example. The problems that exist in SMA Tamansiswa Pematangsiantar are how to manage the physical environment, how to manage the social environment, and what the role of the principal is in managing the school climate to support teacher performance. Qualitative research methods with interviews and data collection data collectors in SMA Tamansiswa. The results of the study found that the school climate gave good results in the physical and social environment in improving teacher performance at SMA Tamansiswa Pematangsiantar.